A method for redistributing virtual machines of heterogeneous data centres - Kuchuk, Nina; Zakovorotnyi, O.; Pyrozhenko, Serhii; Radchenko, Viacheslav; Kashkevich, Svitlana (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article presents the developed algorithm for redistributing virtual machines, based on the ant colony metaheuristics, which provides obtaining a migration matrix of virtual machines, differing from known algorithms by taking into account the heterogeneous structure of data centers and additional resources, which represent overhead costs required by the algorithms of virtual machines Live Migration, when calculating it. The developed support system provides flexibility, scalability and a high degree of adaptation to the conditions of modern heterogeneous data centers. It provides the ability to centralize management and monitoring, while supporting the requirements of cross-platform and integration with existing monitoring solutions, which makes it an important tool for ensuring the reliability and efficiency of data centers. The redistributing virtual machines support system not only simplifies the tasks of administrators, but also promotes more rational use of computing power, which is especially important in the context of today's dynamic development of IT infrastructure.

У статті представлено розроблений алгоритм перерозміщення віртуальних машин, заснований на метаевристиці мурашиної колонії, що забезпечує отримання матриці міграції віртуальних машин, що відрізняється від відомих алгоритмів з урахуванням її розрахунку гетерогенної структури центру обробки даних і додаткових ресурсів, що становлять накладні витрати, необхідні алгоритмам. Розроблена система підтримки забезпечує гнучкість, масштабованість та високий ступінь адаптації до умов сучасного центру обробки даних. Вона надає можливість централізованого управління та моніторингу, підтримуючи при цьому вимоги кросплатформенності та інтеграції з існуючими рішеннями в галузі моніторингу, що робить її важливим інструментом для забезпечення надійності та ефективності роботи центру обробки даних. Система підтримки перерозміщення віртуальних машин не лише спрощує завдання адміністраторів, а й сприяє раціональнішому використанню обчислювальних потужностей, що особливо важливо в умовах сучасного динамічного розвитку IT-інфраструктури.
Метод перерозподілу віртуальних машин гетерогенних центрів обробки даних
Keywords: data center; virtual machines; computer systems; ant algorithms; heterogeneity; віртуальні машини; комп'ютерні системи; мурашині алгоритми; гетерогенність; центри обробки даних